DESIGNING INFORMATION VISUALIZATION FOR HIGHER EDUCATION INSTITUTIONS: A PRE-DESIGN STUDY (Journal of Information and Communication Technology, 2016)
The multidimensionality of students’ data and the limitations of the currently-used data management tools in higher education institutions (HEIs) have been identified as causes of constrained decision-making process in the domain. This, therefore, necessitates a pre-design study for the HEI students’ data-focused InfoVis. The objectives of this study are to identify the prevailing practices of HEI data management, the data analytics methods that are generally employed by HEI data analysts and the comprehensive dimensions that are related to HEI students and adequate for conveying the domain explicit knowledge preferences. A mixed method approach with survey questionnaire and interview as data collection methods, is used. The contributions of this study, among others, are: (i) identification of the pattern and relationship of the domains explicit knowledge preferences; and (ii) the elicitation and description of students’ data dimensions. These are expected to form the basis for the choice and implementation of the content delivery techniques in designing the domain-focused InfoVis. Our future works therefore entail developing the HEI InfoVis conceptual framework, designing the HEI students’ data-focused InfoVis and conducting its users’ experimental evaluation.